Winning Florida : How the Bush Team Fought the Battle. - Zelnick, Robert (Hoover Institution Press publication, 2001)
With a reporter's keen eye for detail, award-winning journalist Zelnick conveys every emotion of the key players in this battle, presenting a rich, colorful tale that reads more like a fictional political thriller than the bizarre real-life drama it was?from election night through the U.S. Supreme Court's historic decision.